Functional properties of human muscle fibers after short-term resistance exercise training - Widrick, Jeffrey J; Stelzer, Julian E; Shoepe, Todd C; Garner, Dena P (American journal of physiology. Regulatory, integrative and comparative physiology, 2002)
Department of Exercise and Sport Science, Oregon State University, Corvallis, Oregon 97331 The aim of this study was to assess the relationships between human muscle fiber hypertrophy, protein isoform content, and maximal Ca 2+ -activated contractile function following a short-term period of resistance exercise training. Six male subjects (age 27 ± 2   yr) participated in a 12-wk progressive resistance exercise training program that increased voluntary lower limb extension strength by >60%. Single chemically skinned fibers were prepared from pre- and posttraining vastus lateralis muscle biopsies. Training increased the cross-sectional area (CSA) and peak Ca 2+ -activated force (P o ) of fibers containing type I, IIa, or IIa/IIx myosin heavy chain by 30-40% without affecting fiber-specific force (P o /CSA) or unloaded shortening velocity (V o ). Absolute fiber peak power rose as a result of the increase in P o , whereas power normalized to fiber volume was unchanged. At the level of the cross bridge, the effects of short-term resistance training were quantitative (fiber hypertrophy and proportional increases in fiber P o and absolute power) rather than qualitative (no change in P o /CSA, V o , or power/fiber volume). resistance training; strength training; muscle hypertrophy; myosin heavy chain; contractile properties